If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2d + -6 = -28 Reorder the terms: -6 + 2d = -28 Solving -6 + 2d = -28 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2d = -28 + 6 Combine like terms: -6 + 6 = 0 0 + 2d = -28 + 6 2d = -28 + 6 Combine like terms: -28 + 6 = -22 2d = -22 Divide each side by '2'. d = -11 Simplifying d = -11
| -9=9(9-5)t | | 3x+7-x=9-10+5x | | 13p+9-4p-6= | | 9x+3x-9x=6+8c-11 | | 3/2y-4=x | | G(x)=log(1)-5 | | s/-(-5)=(-3/9) | | h(t)=-16t^2+48t+640 | | s/(-5)=(-3/9) | | h(t)=-16t^2+200t+20 | | 24x-5=5 | | 1/x=1/3 | | log^2x-1logx=0 | | log^2x-logx=0 | | 5.7*0.03= | | 81x=36x | | 23.5*0.04= | | 12000+r^6=24000 | | 9/9x=3/9 | | 12000+12000r^6=24000 | | 2x+6y-2z+11=0 | | 15p/(1-3p)^2 | | x+5+x=28 | | 3x+x=w | | 4x^2+5x+95x=0 | | 3(X-5)=X-1 | | z^3=-125i | | 2x^2+50=9 | | 5+4a-(4a+3)-(5a+9)= | | (5b-4)=10b | | 2(x-4)-3(x+3)=2x-2 | | 2(x+3)-4(x-3)=8 |